Espécies do gênero Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) em caprinos leitros mantidos em sistema intensivo na região de São Jose do Rio Preto, estado de São Paulo, Brasil. - Freitas, Fagner Luiz da C; Almeida, Katyane de S; Nascimento, Adjair A do; Machado, Célio R; Veschi, Josir L A; Machado, Rosangela Z (My University, 2005)
Were examined 58 dairy goats, 41 kids and 17 adults, Saanen and Alpine breeds, males and females, in intensive system, in the São José do Rio Preto region, São Paulo state, for detection and identification of Eimeria spp. oocysts. The 58 feces samples analyzed by the Centrifugal-flotation technique, were positive for, at least, one Eimeria species. The Eimeria species found in this research were: E. ninakohlyakimovae (77,6%), E. jolchijevi (72,4%), E. alijevi (63,8%), E. christenseni (63,8%), E. arloingi (62,1%), E. caprovina (56,9%), E. hirci (50,0%) and E. caprina (48,3%). It follows that the high rate of the positive animals and the high frequency of the Eimeria species among the animals demonstrated that the disease is common in dairy goats, kids and adults, in intensive system.
Species of the genus Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) in dairy goats maintained in intensive system in the São José do Rio Preto region, São Paulo State, Brazil
Keywords: animal; animal disease; animal husbandry; Brazil; coccidiosis; Eimeria; female; goat; goat disease; isolation and purification; male; methodology; oocyst; parasitology; Animal Husbandry; Animals; Coccidiosis; Female; Goat Diseases; Goats; Male; Oocysts